Grounding strategies in ESL learner-learner interaction / Rushita Ismail and Sarjit Kaur - Ismail, Rushita; Kaur, Sarjit (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
It is considered that insufficient second language vocabulary is one of the challenges facing language learners in daily conversations. Lexical problems occur frequently in ESL face-to-face oral interactions when there is insufficient linguistic competence among second language learners. This paper examines the strategies used by eight dyads of Malaysian ESL learners and interlocutors to collaborate in oral interaction and investigates the existing collaborative behaviours the speaking interlocutors have, the types of grounding strategies they use and the amount of collaborative support they offer to the learners when lexical difficulty arises. The results showed that lexical problems in oral interaction were collaboratively solved. When a lexical difficulty arose and a communication strategy needed to be used, interlocutors resorted to different types of grounding strategies to collaborate with the learner in the successful communication of the message. This paper also highlights the possible implications of this strategic behaviour for the second language learning process.